What Could Posturography Tell Us About Balance Problems in Parkinson's Disease?. Issue 9 (October 2016) - Rossi-Izquierdo, Marcos; Soto-Varela, Andrés; Ernst, Arne; Rubio-Rodríguez, Juan Pedro; Santos-Pérez, Sofía; Sesar, Ángel; Alberte-Woodward, Miguel; Guijarro-Del Amo, Mónica; Román-Rodríguez, Elena San; Faraldo-García, Ana; Zubizarreta-Gutiérrez, Alfonso; Basta, Dietmar
Abstract : Objective: Impaired balance in patients with Parkinson's disease (PD) leads to loss of balance and frequent falls. Computerized dynamic posturography allows the assessment of stance tasks whereas mobile posturography analyzes the balance in free-field conditions, where falls among PD patients commonly occur (e.g. sitting down or standing up). The aim of the present study is to assess postural stability in PD patients with both techniques. Study Design: Prospective study. Setting: University Hospitals, ambulatory care (outpatient clinic). Patients: Thirty-three patients diagnosed with idiopathic PD. Intervention: Balance assessment. Main Outcome Measures: Dizziness handicap inventory (DHI), activities-specific balance confidence scale (ABC), composite score of sensory organization test (SOT), results of free-field body sway analysis (standard balance deficit test (SBDT)), or geriatric SBDT. Results: PD patients showed a significantly higher sway in the roll direction in almost all of the SBDT conditions. Also, pathological sway compared with normative values was more prominent in complex tasks. There is a significant correlation between the different objective variables of the postural study (SOT and SBDT) and the ABC, but not with the DHI. Finally, the percentage of PD patients with a pathological score in SOT-composite score was 54.5% whereas in SBDT-composite score it was significantly higher (93.9%). Conclusion: Mobile posturography is more accurate in depicting the reality of balance impairment in PD patients than platform posturography. Also, ABC relates better than DHI to the significant psychological consequences of balance impairments. An increased lateral trunk sway seems to be a key factor of postural instability in PD patients.